Efeitos da centralização e descentralização no processo brasileiro de municipalização: o caso da região norte - Marília Steinberger (El Colegio Mexiquense, A.C., 2006)
The period of decentralisation, starting with the Constitution on 1988, generated an intense territorial fragmentation in the country, in particular, within the Northern Region. A comparative study of the life quality in both the old and new municipalities in this region has shown that in the majority of the new ones, contrary to what was expected, there was an improvement. This fact, besides contributing to demystify the idea of the creation of new municipalities as a negative factor for the population, highlights a different aspect in the traditional debate that relates this creation with the local interests of obtaining more resources from the Central Government, and thus reinforces their financial dependency.